23.2k views
0 votes
F(x) =x^2-4x+2 and g(x) =3x-7 find (fog)(x)​

2 Answers

3 votes

Answer:

Explanation:

hello :

F(x) =x²-4x+2 and g(x) =3x-7

(fog)(x)​=f(g(x))=f(3x-7) = (3x-7)²-4(3x-7)+2

(fog)(x)​= 9x²-42x+49-12x+28+2

in standard form : (fog)(x)​= 9x²-54x+79

User Neonigma
by
5.6k points
3 votes

Answer:

9x² - 54x + 79

Explanation:

To find (f ○ g)(x) substitute x = g(x) into f(x), that is

f(g(x))

= f(3x - 7)

= (3x - 7)² - 4(3x - 7) + 2 ← expand factor using FOIL

= 9x² - 42x + 49 - 12x + 28 + 2 ← collect like terms

= 9x² - 54x + 79

User Leonel
by
5.4k points